Eksploatacja dna morskiego i podglebia w świetle konwencji NZ o prawie morza - Hołowiński, Jan (Wydział Prawa i Administracji UAM, 1983)
The Polish delegation signed the UN International Convention on the Law of the Sea in December 1982 and its ratification is being prepared now. This international act is evaluated as a compromise, as it often happens with international problems of economic* exploitation, of the sea, of its ground (bed) and of the riches underneath the sea bed. The author of the present contribution presents some critical remarks concerning the concept of the (so-called) Sea Bed Authority, and particularly of the Sea Bed Enterprise, which are supposed to be organs of the United Nations Organization, and ergo are to be considered as subjects of international public Law. At the same time these organs are supposed to enter into commercial contracts with contractors and suppliers of various goods, services and know-how, both private, State owned or mixed companies, whether national or transnational. The UN Convention introduces also new words and phrases in international law which are derived from commercial activity in trade and industrial production, but have no counterpart in commercial law, id est a branch of private law. There is no transmission from this private law to relations regulated by international public law. ln consequence the prescriptions of the Convention do not seem to be practical enough and, even if the Convention will be ratified by a sufficient number of states to make it enforcable, the chapter on exploitation of the sea bed and its underground will have to be conceived in a different way.
See bed exploitation in the light of the United Nations Convention on the Law of the Sea